Soybean root growth and activity as affected by the production system - Pivetta, Laércio Augusto; Castoldi, Gustavo; dos Santos, Gabriel Peixoto; Rosolem, Ciro Antonio (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess winter and spring crop effects on soybean root system growth, and on yield, and to compare a direct method (soil core sampling) with an indirect method (with rubidium) in evaluating the root system. The experimental design was a randomized complete block design, in a split-plot arrangement, with four replicates. Plots consisted of the winter crops, triticale (X Triticosecale) and sunflower (Helianthus annuus), and subplots of the spring crops, pearl millet (Pennisetum glaucum), forage sorghum (Sorghum bicolor) and sunn hemp (Crotalaria juncea), besides chisel tillage in 2003 and 2009. Soybean (Glycine max) was grown in the summer, and its root system was evaluated by physical sampling of the roots and by root activity assessment using rubidium. Changes in the architecture or in the activity of soybean roots did not affect yield. The distribution and activity of soybean roots were not significantly affected by the winter cover crops, but root growth was favored after millet and sorghum were grown in the spring. The direct measurement of the soybean root system with an auger has low correlation with root activity.